Resisting the White Possessive: Elsa Laula and Karin Stenbergs contributions to theorising Nordic racism - Svendsen, Stine H. Bang (Septentrio Conference Series, 2019)
At the turn to the 20th century settler colonialist and racist policies of land theft and systematic devaluation of Sámi livelihoods had produced an acute and dire political situation in Sápmi. Elsa Laula (1877-1931) and Karin Stenberg (1884-1969) were central activists and writers in the anticolonial Sámi national movement that organised in the south of Sápmi at this time. The political analyses in Laula´s book Inför lif eller död (1904) and Stenberg and collegues´ Dat läh mijen situd! (1920) offer scathing critiques of the settler colonial racism of the Swedish state at the time. Their contributions theorize the relationship between whiteness and property in the colonization of Sápmi, and the crucial role that racialization of the Sámi people have played in this process. These theoretical contributions are largely unknown to Nordic feminist scholarship on race and racism, however. In this paper I show how Laula and Stenberg´s analysis of racism offered insights that feminists would lend from American and British black feminist scholarship, as well as Australian indigenous feminism almost a hundred years after they were first formulated in the Nordic context. Finally, I consider possible reasons for the denial of this scholarly history in Nordic feminism. Merk: Selv om abstractet er på engelsk kan jeg godt holde innlegget på norsk.